THE IMPACT OFWHATSAPP MOBILE SOCIAL LEARNING ON THE ACHIEVEMENT AND ATTITUDES OF FEMALE STUDENTS COMPARED WITH FACE TO FACE LEARNING IN THE CLASSROOM - Amry, Aicha Blehch (European Scientific Journal, ESJ, 2014)
The use of mobile learning activities in learning and teaching online course is an innovative educational technology in higher education. The study seeks to explore the impact of using WhatsApp mobile learning activities on the achievement and attitudes of online students using mobile devices at the university. Researcher conducted an experiment in the 2014 academic year. Specifically, this study compares an independent sample of students in an experimental group (15 students) with a control group (15 students) from a university class. The e-learning process of the experimental group is based on WhatsApp mobile learning activities. The e-learning process of the control group is without WhatsApp mobile learning activities and receives only face-to-face learning in the classroom. A learning unit of the same course educational media is experimented with the experimental and control group. The t-test was used to compare the differences between the experimental and control groups. The results of the experimentation show that there are real differences, at 0.05 alpha level, in the achievements and attitudes of the experimental group compared with the control group.